2023
DOI: 10.3389/fbioe.2023.1215518
|View full text |Cite
|
Sign up to set email alerts
|

Spotlights on extracellular vesicles in hepatocellular carcinoma diagnosis and treatment: an update review

Abstract: Hepatocellular carcinoma (HCC), one of the most prevalent cancers, with a high mortality rate worldwide, seriously impairs patient health. The lack of accurate targets impedes the early screening and diagnosis of HCC and is associated with a poor response to routine therapies. Extracellular vesicles (EVs), comprising exosomes, microvesicles, and apoptotic bodies, are lipid bilayer membrane-derived nanometer-sized vesicles. EVs can be secreted from various cancer cells and release diverse biomolecules, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The therapeutic potential of EVs in HCC is a subject of increasing scientific interest and holds promise for innovative diagnostic and therapeutic interventions [32,143,144]. Within the context of HCC, EVs have emerged as key players in the intricate network of intercellular communication within the tumor microenvironment [15,145,146].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of EVs in HCC is a subject of increasing scientific interest and holds promise for innovative diagnostic and therapeutic interventions [32,143,144]. Within the context of HCC, EVs have emerged as key players in the intricate network of intercellular communication within the tumor microenvironment [15,145,146].…”
Section: Discussionmentioning
confidence: 99%
“…The complete analysis and screening of urinary EVs revealed that the glycoproteins LG3BP, PIGR, and KNG1 were highly elevated in these EVs obtained from the urine of HCC patients, but ASPP2 was dramatically reduced in these EVs. 222 SMAD3, one of the molecules involved in HCC metastasis, also offers diagnostic potential for HCC, discriminating HCC from healthy to benign hepatoma 223 .…”
Section: Sources Of Extracellular Vesiclesmentioning
confidence: 99%
“…Likewise, it has been demonstrated that miR-638 in EVs is a diagnostic for HCC diagnosis and an independent predictive factor for HCC patients. 222 …”
Section: Sources Of Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is an option for patients with advanced HCC, but insensitivity to chemotherapeutic agents leads to poor treatment outcomes. Moreover, resistant cells secrete and deliver exosomes to sensitive cells, facilitating angiogenesis and EMT, further inducing multidrug resistance [134]. Thus, exosome-based treatments for tumor resistance appear feasible and have achieved preliminary efficacy in colorectal cancer [135][136][137], although such treatments have not yet been reported in hepatitis B-related liver cancer.…”
Section: Exosomes Regulate Drug Resistance In Hepatitis B Liver Cancermentioning
confidence: 99%